Nondestructive evaluation of grout defects in internal tendons of post-tensioned girders. (October 2018) - Terzioglu, Tevfik; Karthik, Madhu M.; Hurlebaus, Stefan; Hueste, Mary Beth D.; Maack, Stefan; Woestmann, Jens; Wiggenhauser, Herbert; Krause, Martin; Miller, Patrick K.; Olson, Larry D.
Abstract: Post-tensioning systems provide safe and efficient construction solutions for long span bridges. Despite the improved grouting practices over the past decade, existing post-tensioning systems may have significant amount of grout defects, which could lead to corrosion of the strands. Condition assessment of post-tensioning systems is necessary to allow bridge owners to take timely, proactive actions to mitigate or prevent further deterioration and unanticipated tendon failures. A detailed experimental study conducted to assess the performance of nondestructive evaluation techniques in detecting grout defects within internal tendons is presented herein. Nondestructive evaluation techniques that include Ground Penetrating Radar, Impact Echo, Ultrasonic Tomography, and Ultrasonic Echo are evaluated in terms of detecting the location and severity of fabricated grout defects in a full-scale post-tensioned U-girder mock-up specimen. While Ground Penetrating Radar can identify the location and profile of the internal tendons, particularly metal ducts due to strong reflections, this method did not provide any information about the defect conditions within the tendon. Both Impact Echo and Ultrasonic Echo techniques are effective in identifying the location of grout defects, but could not differentiate between water, void, or compromised grout conditions. The study clearly demonstrates the need for NDE techniques that are applicable to anchorage regions, and that are capable of estimating the severity and nature of grout defects in internal tendons.